Simultaneous kidney and pancreas transplant - López, Daniel; Pose, Juan; Fleitas, Gabriela; Andreoli, Gustavo; Caviglia, Pablo; Orihuela, Sergio; Gómez Fossati, Carlos (Cirugía del Uruguay, 2003)
Simultaneous kidney and pancreas transp/ant is a currently accepted alternative for treatment of diabetic nephropathy in the stage of renal function substitution. Within the framework of participation of Surgical Clinic "B" in trasplant activities in the University Hospital, the paper describes in detail the configuration of a multidisciplinary team for implementation of a reno-pancreatic transplant program. This preliminary report óf the team's initial experience with this procedure sets forth indications for transplant, selection criteria and particular aspects of the technique employed for extracting and implanting and graft